Roseomonas mucosa-Induced Peritonitis in a Patient Undergoing Continuous Cycler Peritoneal Dialysis: Case Report and Literature Analysis. (1st November 2021) - Roy, Sasmit; Patel, Sumit; Kummamuru, Hardhik; Garcha, Amarinder Singh; Gupta, Rohan; Adapa, Sreedhar
Abstract : Roseomonas species, a rare Gram-negative microorganism, has seldom been reported to cause peritonitis in end-stage renal disease patients on peritoneal dialysis. Only seven cases of peritonitis by this rare microorganism have been reported worldwide. Treatment options can be challenging if not detected early and can lead to significant morbidity and mortality along with the switching of the dialysis modality to hemodialysis which is highly undesirable. Our patient is a 65-year-old Caucasian female who needed to be changed to emergency hemodialysis due to inability to perform peritoneal dialysis from suspected peritonitis and was subsequently discovered to have peritonitis from Roseomonas mucosa . She recovered with a prolonged antibiotics course and returned to peritoneal dialysis in 3 months following her treatment completion. Prompt diagnosis and prolonged antibiotics are a cornerstone in the management of this rare microorganism to prevent mortality and morbidity from peritonitis.